Echinochloa spp response to preemergence and postemergence herbicides in California rice (Oryza sativa L.) - Vulchi, Rohith; Guan, Taiyu; Clark, Troy; Brim-DeForest, Whitney (Frontiers in Agronomy, 2024)
Historically, herbicides were used for Echinochloa spp control in California rice production which led to the selection of herbicide-resistant biotypes. Field surveys were conducted across the seven major rice-growing counties in 2020 and Echinochloa spp samples including barnyardgrass (Echinochloa crus-galli (L.) P.Beauv.), junglerice (Echinochloa colona (L.) Link), late watergrass (Echinochloa oryzicola (Vasinger) Vasinger) and coast cockspur (Echinochloa walteri (Pursh) Heller) were collected. Greenhouse experiments were carried out to determine their suspected resistance to common preemergence and postemergence rice herbicides used in California in Fall and Winter of 2021. A total of 62 and 63 samples were characterized for suspected resistance to four preemergence granular and three postemergence foliar-applied herbicides, respectively.When granular herbicides were evaluated, samples suspected of resistance in Winter were a subset of samples that were suspected of resistance in Fall. Results indicate >90% of Echinochloa spp samples were resistant to thiobencarb, benzobicyclon + halosulfuron and penoxsulam when combined across species and counties. Cross-resistance between benzobicyclon + halosulfuron and penoxsulam was observed in >90% of the samples when combined across species and counties. Suspected clomazone resistance was observed in <75% of the samples when combined across species and counties. Suspected resistance to cyhalofop and propanil was observed in <50% of the samples when averaged across both runs. Multiple-resistance to foliar herbicides ranged from 48-60% of the samples across species and experimental runs. These results indicate the necessity for rotating herbicides during alternate cropping seasons and emphasizing integrating non-chemical strategies for Echinochloa spp control in California rice production.